Nota dos Editores - Silva, Carlos; Ferreira, Joana; Ribeiro, Mariana; Magalhães, Violeta Amélia; Rebouças, Rute (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2021)
.